Cross-Cultural Adaptation and Validation of the Portuguese Version of the Physical Therapy Outpatient Satisfaction Survey - Cavalheiro, Luís M. (2017)
The aim of this study was to adapt and validate the Physical Therapy Outpatient Satisfaction Survey (PTOPS) for the Portuguese culture. This version was obtained by a forward/ backward translation, consensus panels, and pre-test. The Portuguese PTOPS was administered to 76 physical therapy outpatients in 10 health services. The content analysis (panels of experts and lay people) and the factor analysis resulted in a reduction of the original 34 items to 28 items that validly identify 3 constructs. The reliability was acceptable for both internal consistency (Cronbach’s alpha = 0.73) and reproducibility (ICC between 0.84 and 0.87), which represent acceptable levels of validity and reliability.